CONSONANT CLUSTERS IN THE SPOKEN ENGLISH OF EREI-ENGLISH BILINGUALS - Ukam, Edadi Ilem; Kadiri, Goodluck C. (EBSU Journal of Social Sciences and Humanities, 2024)
The ability to articulate consonants in clusters enhances communicative intelligibility, but much linguistic attention has not been paid to them, especially in a second language (L2) situation. Previous studies (e.g. Lo, 2001; Gut, 2007; Chen, 2011; Rungruang, 2017) mainly focused on either the onset or coda clusters in an attempt to show the problems faced by L2 learners’ production. The current study investigates the handling of onset and coda consonant clusters in the speech of Erei-English speakers. Chest pulse and sonority theories were adopted as theoretical frameworks, while ten subjects and 17 tokens were selected for the study. The tokens were read aloud by the subjects, recorded, saved and subjected to Praat for analysis. The findings reveal that Erei-English speakers used two strategies to modify and simplify the production of English consonant clusters: consonant deletion and vowel insertion. The subjects found it difficult to produce two or more consonants in succession at both onset and coda positions. They not only deleted any consonant in a cluster, they also inserted a vowel(s) in-between a cluster to simplify it; a rehash of their Erei mother tongue. The study concludes that strong first language influence is the major cause of Erei-English speakers’ poor performance of the correct production of consonant clusters.